1998
DOI: 10.1128/mcb.18.8.4855
|View full text |Cite
|
Sign up to set email alerts
|

Premature Translation of oskar in Oocytes Lacking the RNA-Binding Protein Bicaudal-C

Abstract: Bicaudal-C (Bic-C) is required during Drosophila melanogaster oogenesis for several processes, including anterior-posterior patterning. The gene encodes a protein with five copies of the KH domain, a motif found in a number of RNA-binding proteins. Using antibodies raised against the BIC-C protein, we show that multiple isoforms of the protein exist in ovaries and that the protein, like the RNA, accumulates in the developing oocyte early in oogenesis. BIC-C protein expressed in mammalian cells can bind RNA in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
77
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(82 citation statements)
references
References 50 publications
5
77
0
Order By: Relevance
“…Drosophila Bic-C has been shown to bind to poly(G) and poly(U) RNAs in pull-down experiments in vitro (Saffman et al 1998;Braddock et al 2002) and a similar preference in RNA binding has been reported for mouse Bic-C (Bouvrette et al 2008). While Bic-C proteins contain several GxxG motifs that are involved in nucleic acid binding in canonical KH domains (Braddock et al 2002), the KH domains of GLD-3 are degenerate in that none features the GxxG sequence (Fig.…”
Section: Rna-binding Properties Of the Gld-3 Kh Regionmentioning
confidence: 99%
“…Drosophila Bic-C has been shown to bind to poly(G) and poly(U) RNAs in pull-down experiments in vitro (Saffman et al 1998;Braddock et al 2002) and a similar preference in RNA binding has been reported for mouse Bic-C (Bouvrette et al 2008). While Bic-C proteins contain several GxxG motifs that are involved in nucleic acid binding in canonical KH domains (Braddock et al 2002), the KH domains of GLD-3 are degenerate in that none features the GxxG sequence (Fig.…”
Section: Rna-binding Properties Of the Gld-3 Kh Regionmentioning
confidence: 99%
“…For example, Bic-C mutant mice develop renal cysts, providing a model for polycystic kidney disease (Maisonneuve et al 2009;Tran et al 2010). In Drosophila, where Bic-C was first identified, Bic-C contributes to patterning of the early embryo by repressing specific maternal mRNAs, such as oskar (Saffman et al 1998;Chicoine et al 2007). However, in vertebrates the mechanisms of Bic-C action have not been identified nor have mRNA targets been identified systematically.…”
Section: Introductionmentioning
confidence: 99%
“…Bicaudal-C (Bic-C) RNA binding proteins have vital roles in vertebrate embryogenesis and also in adult tissues, including the kidney, heart, and pancreas (Saffman et al 1998;Chicoine et al 2007;Gamberi and Lasko 2012). For example, Bic-C mutant mice develop renal cysts, providing a model for polycystic kidney disease (Maisonneuve et al 2009;Tran et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Drosophila has homologs of some of these proteins, and Drosophila's CPEB (named Orb) has been shown to interact with Bic-C, the Drosophila homolog of GLD-3 (Castagnetti and Ephrussi 2003). Bic-C, which is present in oocytes and early embryos like wisp, is required for anteriorposterior patterning during oogenesis (Mahone et al 1995;Saffman et al 1998). In the germline, Bic-C has been recently reported to regulate the expression of specific mRNAs by participating in control of their poly(A) tail length (Chicoine et al 2007).…”
mentioning
confidence: 99%